การพัฒนาความสามารถในการออกแบบการเรียนการสอนที่บูรณาการหลักปรัชญาของเศรษฐกิจพอเพียงกับสาระรายวิชาด้วยโปรแกรมฝึกอบรมที่ใช้แนวคิดการศึกษาแบบเน้นผลลัพธ์และการเรียนรู้เชิงรุก - ฐนัส มานุวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
This study consisted of two objectives as follows: 1) to develop a training program using outcome-based education and active learning in developing the abilities to design an instruction that integrates the Sufficiency Economy Philosophy into learning strands and 2) to study the effectiveness of the training program. This study was an action research study. The participants included eight university lecturers working in a military educational institute. The data were collected using 1) interviews (2) behavior observations (3) tests and questionnaires and (4) self-learning reflection notes during the implementation of the three-week training program. The data were analyzed using content analysis, analytic induction, and data display.The results for the first research objective showed that the training program’s objective was to develop the ability to design an instruction that integrates the Sufficiency Economy Philosophy into learning strands. The principles, objectives, learning outcomes, and assessment were designed based on the outcomes-based education approach and the activities were designed based on the active learning approach. The training program included three phases. Phase I: Goal setting, the participants identified the individual goal and common goal in attending the training program. Phase II: Collaborative Design, the participants worked collaboratively to design an instruction. Phase III: Reflection, the participants reflected on the learning experiences and planned for future improvement. Regarding the effectiveness of the training program, the results showed that the participants showed development in their ability to design an instruction that integrates the Sufficiency Economy Philosophy into learning strands in all nine aspects. Their development reflected the identity of the principles of the training program which were balanced instructional resource management, collaborative development, and instructional design that considers morals, ethics, and environmental value.